High pentraxin 3 level predicts septic shock and bacteremia at the onset of febrile neutropenia after intensive chemotherapy of hematologic patients - Matti Vänskä; Irma Koivula; Sari Hämäläinen; Kari Pulkki; Tapio Nousiainen; Esa Jantunen; Auni Juutilainen (Haematologica, 2011)
We evaluated pentraxin 3 as a marker for complications of neutropenic fever in 100 hematologic patients receiving intensive chemotherapy. Pentraxin 3 and C-reactive protein were measured at fever onset and then daily to day 3. Bacteremia was observed in 19 patients and septic shock in 5 patients (three deaths). In comparison to C-reactive protein, pentraxin 3 achieved its maximum more rapidly. Pentraxin 3 correlated not only with the same day C-reactive protein but also with the next day C-reactive protein. High pentraxin 3 on day 0 was associated with the development of septic shock (P=0.009) and bacteremia (P=0.046). The non-survivors had constantly high pentraxin 3 levels. To conclude, pentraxin 3 is an early predictor of complications in hematologic patients with neutropenic fever. High level of pentraxin 3 predicts septic shock and bacteremia already at the onset of febrile neutropenia. (ClinicalTrials.gov Identifier: NCT00781040.)